ERASER: a thrombectomy study with predictive analytics end point - Fiehler, Jens; Möhlenbruch, Markus Alfred; Bendszus, Martin (Stroke, 2019)
Background and Purpose—Using a novel study design with virtual comparators based on predictive modeling, we investigated whether next-generation mechanical thrombectomy devices improve outcomes in patients with ischemic stroke. We hypothesized that this new study design shows that a next-generation mechanical thrombectomy system is superior to intravenous tPA (tissue-type plasminogen activator) therapy (IVT) alone.Methods—ERASER (Eric Acute Stroke Recanalization) was an investigator-initiated, prospective, multicenter, single-arm (virtual 2-arm) study that evaluated the effectiveness of a new recanalization device together with a specific intermediate catheter (Embolus Retriever with Interlinked Cages/SOFIA, Microvention) in stroke patients with internal carotid artery or middle cerebral artery occlusions. The primary end point was the volume of saved tissue. Volume of saved tissue was defined as the difference of actual infarct volume and brain volume predicted to develop infarction using a machine learning model based on data from intravenous tPA therapy patients.Results—Eighty-one patients were enrolled. The median patient age was 71 years (interquartile range, 61-77). National Institutes of Health Stroke Scale score was 14 (interquartile range, 12-18). The actual infarct volume was smaller than predicted by the intravenous tPA therapy model, with a median volume of saved tissue of 50 mL (interquartile range, 19-103; P<0.0001). Good clinical outcome (modified Rankin Scale, 0-2 at 90 days) was observed in 48 out of 69 (70%). The recanalization rate (Thrombolysis in Cerebral Infarction 2b/3) was 95%.Conclusions—ERASER is the first mechanical thrombectomy study with a primary end point based on predictive analytics enabling intraindividual virtual comparisons. The next-generation mechanical thrombectomy method resulted in smaller infarcts than predicted after intravenous tPA therapy alone and showed a high rate of good clinical outcome. The novel study design with virtual comparisons is promising for further application and testing in the neurovascular arena.Clinical Trial Registration—URL: https://www.clinicaltrials.gov. Unique identifier: NCT02534701.
Gesehen am 20.07.2019